2017
DOI: 10.1080/09637486.2017.1283681
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pasteurisation and freezing method on bioactive compounds and antioxidant activity of strawberry pulp

Abstract: This study evaluated the stability of strawberry pulp subjected to three factors, pasteurisation (pasteurised and unpasteurised), freezing method (static air and forced air) and storage time (0, 2, 4 and 6 months). Pasteurisation favoured vitamin C retention during storage but enhanced the total loss of phenolics without affecting anthocyanin levels. Freezing by forced air was more effective in retaining phenolics during the first 4 months of storage, although the freezing method did not affect the anthocyanin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 32 publications
4
11
0
Order By: Relevance
“…The results are in line with Goncalves et al. (2017) in strawberry pulp. They concluded that heat treatment led to a greater loss of total phenols.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…The results are in line with Goncalves et al. (2017) in strawberry pulp. They concluded that heat treatment led to a greater loss of total phenols.…”
Section: Resultssupporting
confidence: 93%
“…The results are in conformity with the findings of Reyes and Cuenca (2010) in Eugenia stipitata Mc Vaugh pulp and Goncalves et al. (2017) in strawberry pulp.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…In general, the freezing process negatively affects the AOA of fruit puree or juices. Gonçalves et al [129], after freezing of strawberry pulp, determined a decrease of the AOA by both DPPH and ABTS on both pasteurized and unpasteurized puree, irrespective of the freezing method applied (−25 • C by forced air or −18 • C by static air). Patthamakanokporn et al [125], after freezing of guava puree at −20 • C, observed a decrease of the AOA by both the ORAC and FRAP assay as well as of the polyphenols content, and this same effect was also observed by Loncaric et al [130], after freezing (12 h; −18 • C) of apple puree (cv.…”
Section: Effect Of Freezing and Freezing Temperaturementioning
confidence: 99%
“…The phenolic compounds generated a UV-Vis spectral result in the HPLC chromatogram at 280 nm. Quantitative determination of compounds was conducted by comparison with dose-response curves based on m/z data from authentic standards of individual polyphenols [14]. The results of three replicates were expressed as mg 100 g -1 (d.…”
Section: Chromatography Analysesmentioning
confidence: 99%